Method for improving water absorption rate of polyphenyl ether resin / hollow glass microsphere composite material and application

By modifying hollow glass microspheres in situ surface and mixing them with polysenol resin, the problem of difficult to reduce the water absorption rate of composite materials is solved, and composite materials with good water absorption rate and water resistance are achieved. They are suitable for high-frequency High-speed communication application.

CN119410124AActive Publication Date: 2025-02-11TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411674077.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-11
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The water absorption rate of existing polyshenol/hollow glass microsphere composites is difficult to further reduce, resulting in limited performance in high-frequency and high-speed communication applications.

Method used

By in situ modification on the surface of hollow glass microspheres, vitrification and sintering using silane coupling agent and precursor particles for glass sintering, surface-modified hollow glass microspheres were prepared and mixed with polystyrene resin. Form a composite material with improved water absorption.

Benefits of technology

The low water absorption rate and good water resistance of composite materials have been achieved. Compared with the preparation methods of certain silane coupling agents, the water absorption rate is reduced by at least 25%, making it more suitable for high-frequency and high-speed communication applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410124A_ABST
    Figure CN119410124A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the water absorption rate of a polyphenyl ether resin / hollow glass microsphere composite material, and in the method, hollow glass microspheres subjected to in-situ surface modification are mixed with polyphenyl ether resin to obtain the composite material with improved water absorption rate. The surface-modified hollow glass microspheres are prepared by adopting an in-situ modification method, and compared with the method that the microspheres are prepared and then modified, the in-situ modification method is higher in efficiency, more suitable for industrial production, capable of avoiding the defects of caking and the like and more beneficial to dispersion in resin. In the prepared composite material, the surface-modified hollow glass microspheres are tightly combined with the polyphenyl ether resin, so that the water absorption rate is extremely low, and the water blocking performance is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a method for improving the water absorption rate of a polyphenylene ether resin / hollow glass microsphere composite material and its application. Background Art

[0002] With the advent of the 5G communication era, substrate materials have become the key to determining the performance of electronic circuits. Polyphenylene ether is widely used in the preparation of high-frequency substrates due to its low water absorption, low dielectric constant, low dielectric loss, and good heat resistance and processing properties. Commonly used modified polyphenylene ethers are terminal hydroxyl or terminal double bond structures. It is used to blend with one or more of epoxy resins, maleimide resins, hydrocarbon resins and cyanate resins to prepare copper clad laminate substrate materials for high-frequency and high-speed communications.

[0003] In the prior art, in order to further reduce the dielectric constant and dielectric loss, hollow glass microspheres and polyphenylene ether are used to prepare copper-clad laminate materials, but its water absorption rate is difficult to further reduce. This is because the silanol groups on the surface of the hollow glass microspheres will adsorb water molecules in the air through the action of hydrogen bonds, thereby causing agglomeration between particles. In addition, hollow glass microspheres are inorganic non-metallic materials with fewer active sites on the surface, making it difficult to bond with the resin and having weak interface bonding, resulting in the difficulty in reducing the water absorption rate of the composite material. This moisture absorption effect will seriously affect its further use. Summary of the invention

[0004] In order to improve the above technical problems, the present invention provides a method for improving the water absorption rate of a polyphenylene ether resin / hollow glass microsphere composite material. Specifically, the method comprises the following steps:

[0005] (1) A liquid system for synthesizing hollow glass microspheres;

[0006] (2) synthesizing precursor particles;

[0007] (3) vitrification sintering: mixing the silane coupling agent with the precursor particles, vitrification sintering, and preparing in-situ surface-modified hollow glass microspheres;

[0008] (4) Mixing the surface-modified hollow glass microspheres with polyphenylene ether resin to obtain a composite material with improved water absorption.

[0009] According to an embodiment of the present invention, the composition of the hollow glass microspheres prepared in step (3) comprises 65-78% SiO2, 8-12% B2O3, 8-12% Na2O, 6-11% CaO, 0.5-2% MgO and 0.5-2% Al2O3, based on a mass ratio of 100%.

[0010] According to an embodiment of the present invention, in step (1), the amount of each raw material added to the liquid system is measured according to the component ratio of the hollow glass microspheres prepared in step (3).

[0011] According to an embodiment of the present invention, in step (1), the feed liquid system includes silicon dioxide, borax, sodium sulfate, sodium nitrate, calcium nitrate, sodium aluminate and magnesium chloride.

[0012] According to an embodiment of the present invention, in step 1), the added amounts of silicon dioxide, borax, sodium sulfate, sodium nitrate, calcium nitrate, sodium aluminate and magnesium chloride are measured according to the component proportions of the hollow glass microspheres prepared in step 3).

[0013] According to an embodiment of the present invention, in step (1), the feed liquid system is evenly dispersed in the homogeneous dispersion system.

[0014] According to an embodiment of the present invention, in step (2), the synthesis temperature of the precursor particles is 350-400 degrees Celsius.

[0015] According to an embodiment of the present invention, in step (3), the silane coupling agent is selected from vinyltrimethoxysilane (A171), vinyltriethoxysilane (A172) or γ-methacryloxypropyltrimethoxysilane (KH570).

[0016] According to an embodiment of the present invention, in step (3), the mass of the silane coupling agent is 1-3% of the precursor particles, for example, 1%, 2% or 3%.

[0017] According to an embodiment of the present invention, step (3) is performed in a vitrification gasification furnace. Specifically, the silane coupling agent is sprayed into the vitrification gasification furnace in a convection manner, mixed with the precursor particles for in-situ modification, and vitrified and sintered to obtain surface-modified hollow glass microspheres.

[0018] According to an embodiment of the present invention, in step (3), the sintering temperature is 700-900°C (e.g., 700, 750, 800, 850 or 900°C).

[0019] According to an embodiment of the present invention, in step (3), the precursor particles

[0020] The flight time in the vitrification vaporization furnace is about several seconds, for example, about 1-2 seconds.

[0021] According to an embodiment of the present invention, in step (4), the mass percentage of the surface-modified hollow glass microspheres in the polyphenylene ether resin is 5-60%.

[0022] According to an embodiment of the present invention, in step (4), glass fiber (specifically low dielectric constant glass fiber or low dielectric constant glass fiber cloth) may be further added, and the prepared composite material may be used as a copper clad laminate substrate.

[0023] Beneficial effects of the present invention:

[0024] (1) In the composite material of the present invention, the surface-modified hollow glass microspheres are tightly bonded to the polyphenylene ether resin, so the water absorption rate is extremely low and the water barrier performance is good. Specifically, for example, compared with the composite material prepared by KH570, the water absorption rate of the composite material prepared by A171 or A172 is at least reduced by 25%.

[0025] (2) The present invention adopts an in-situ modification method to prepare the surface-modified hollow glass microspheres. Compared with the modification after the microspheres are prepared, the in-situ modification method is more efficient, avoids defects such as agglomeration, and is more conducive to dispersion in the resin.

[0026] (3) The in-situ modification method of the present invention is more suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a SEM image of the composite material of Example 4.

[0028] Figure 2 It is the dielectric loss (Df diagram) of the composite materials of Example 1 and Example 3 under high temperature and high humidity conditions.

[0029] Figure 3 is the dielectric constant (Dk diagram) of the composite materials of Example 1 and Example 3 under high temperature and high humidity conditions. DETAILED DESCRIPTION

[0030] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0031] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0032] Example 1

[0033] (1) The composition of the hollow glass microspheres of the present invention is as follows: the content of silicon dioxide is 73% (weight ratio, the same below). The silicon dioxide is dispersed in an aqueous solution with a solid content of 15%. Under stirring conditions, soluble salts equivalent to 9% B2O3, 9% Na2O, 7.2% CaO, 0.9% MgO and 0.9% Al2O3 of glass matrix material, including borax, sodium sulfate, sodium nitrate, calcium nitrate, sodium aluminate and magnesium chloride, are added in sequence. After stirring for 30 minutes, the mixture is sent into an AB double reactor and switched to a homogenizing dispersion system for dispersion for 60 minutes to perform a homogenizing dispersion treatment of the slurry.

[0034] (2) The dispersed slurry is transported to a high-speed atomizer through a diaphragm pump, and after contacting with a parallel high-temperature drying medium (350-400 degrees Celsius), it is dried into precursor particles in a short time.

[0035] (3) Subsequently, the dried precursor particles were sent to an in-situ vitrification gasification furnace, and at the same time, 2% mass concentration of silane coupling agent A171 was sprayed into the vitrification gasification furnace by convection for in-situ modification, vitrification sintering, the sintering temperature was 800°C, the particle flight time was 1-2 seconds, and the surface-modified hollow glass microspheres were obtained. The prepared hollow glass microspheres were tested for density using a true density meter, and the true density was 0.46 g / cm 3 According to the industry standard JC / T2285-2014, the pressure resistance test is carried out using an isostatic pressure test system, and the pressure resistance strength can reach 10,000 psi. The single output of the surface-modified hollow glass microspheres can reach hundreds of kilograms.

[0036] (4) Mixing the surface-modified hollow glass microspheres with polyphenylene ether resin to obtain the composite material.

[0037] Example 2

[0038] The difference between Example 2 and Example 1 is that the silane coupling agent used is A172.

[0039] Example 3

[0040] The difference between Example 3 and Example 1 is that the silane coupling agent used is KH570.

[0041] Example 4

[0042] The difference between Example 4 and Example 1 is that step (4) is different:

[0043] (4) Preparation of copper clad laminate substrate

[0044] Among them, low dielectric constant glass fiber cloth is included, and the specific steps include:

[0045] a. Ingredients: Mix polyphenylene ether resin, curing agent, accelerator, additive, etc., add the surface-modified hollow glass microspheres obtained in step (3), and stir evenly, wherein the mass proportion of the hollow glass microspheres in the resin is 5%-60%, for example, 20%;

[0046] b. Gluing: impregnating the glass fiber cloth with low dielectric properties into the resin and hollow glass microspheres obtained in step a, and then drying at a certain temperature to form a prepreg;

[0047] c. Assembly: Lay the prepregs together according to the design;

[0048] d. Hot pressing: put the assembled prepreg into the hot press, set the temperature and pressure conditions, and press into shape;

[0049] e. Processing: Mechanically process the hot-pressed composite sheet to obtain the desired shape.

[0050] Figure 1 is a SEM image of the copper-clad laminate substrate of Example 4, Figure 1 In the figure, the circles are beads, the wavy lines are low-dielectric glass fiber cloth, and the other parts are polyphenylene ether resin.

[0051] Comparative Example 1

[0052] (1) Surface modification of hollow glass microspheres with silane coupling agent: First, prepare an alcohol-water mixed solution with a volume ratio of ethanol to distilled water of 9:1, adjust the pH of the alcohol-water mixed solution to 4.5-5.5 with acetic acid, and add silane coupling agent KH570 to a concentration of 2% under stirring. Take 60g of hollow glass microspheres T46 and add them to 300mL of the above KH570 modifier solution, stir them with electromagnetic stirring at room temperature for 1h, then filter the microspheres with a vacuum filter, put them in an oven, and dry them at 80°C for more than 2h to obtain a T46-KH570 hollow glass microsphere sample, i.e., modified hollow glass microspheres.

[0053] Comparing Example 1 with Comparative Example 1, it can be seen that in the method of Comparative Example 1, the single output of the modified hollow glass microspheres is only tens of grams, which cannot be industrialized; while the single output of the method of the present invention can reach hundreds of kilograms, which can fully meet the industrialization requirements.

[0054] Water absorption test

[0055] The composite materials prepared in Examples 1-3 were subjected to a high pressure cooking method (PCT) to quickly determine the water absorption rate. The specific test process is as follows:

[0056] 1. The sample size is (50±1)mmx(50±1)mmx1.6m. There are 3 samples of each type. Wipe them with a clean wet cloth for more than three times to make them clean.

[0057] 2. Place the sample in an oven and dry it at 105-110℃ for 1h. After taking it out, place it in a desiccator and cool it to room temperature. Weigh it immediately after taking it out of the desiccator and record it as m1, accurate to 0.1mg.

[0058] 3. Cover the pressure cooker with enough water but do not seal it, and heat the water to boiling without pressure. Open the lid and quickly place the weighed sample vertically on the sample rack in the pressure cooker, so that the sample is suspended vertically above the boiling water. Be careful not to let the samples touch each other or touch the wall of the pressure cooker. The heating time is controlled within 7+2 / -0min. After the pressure (gauge pressure) reaches 103.4±3KPa, keep it for 1 hour. After the cooking is completed, cool and discharge the gas of the pressure cooker according to the method recommended by the manufacturer. After the pressure is completely released, open the high-pressure container, carefully take out the hot sample in the pressure cooker, wipe the sample with a dry cloth and weigh it immediately, and record it as m2, accurate to 0.1mg.

[0059] 4. Calculation

[0060] The water absorption of the sample is calculated according to the following formula, accurate to 0.01%.

[0061] Water absorption rate = (m2-m1) / m1×100%

[0062] The water absorption rates of the composite materials of Examples 1-3 are 0.15%, 0.15% and 0.20% respectively. Compared with Example 3, the water absorption rates of Examples 1 and 2 are reduced by 25%.

[0063] Dielectric loss and dielectric constant testing under high temperature and high humidity conditions

[0064] The dielectric loss and dielectric constant of the composite materials prepared in Examples 1 and 3 were tested after being treated at high temperature (85°C) and high humidity (85% RH) for different days. The test results are as follows: Figure 2 and Figure 3 shown.

[0065] Figure 2 and Figure 3 It can be seen that the dielectric loss and dielectric constant of the composite material modified by A171 in Example 1 are more stable than those of KH570 after being subjected to 85% RH 85°C wet heat aging treatment for different days.

[0066] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for improving the water absorption of a polyphenylene ether resin / hollow glass microsphere composite material, characterized in that: The method comprises the following steps: (1) A liquid system for synthesizing hollow glass microspheres; (2) synthesizing precursor particles; (3) vitrification sintering: mixing the silane coupling agent with the precursor particles, vitrification sintering, and preparing in-situ surface-modified hollow glass microspheres; (4) Mixing the surface-modified hollow glass microspheres with polyphenylene ether resin to obtain a composite material with improved water absorption.

2. The method according to claim 1, characterized in that The composition of the hollow glass microspheres prepared in step (3) includes 65-78% SiO2, 8-12% B2O3, 8-12% Na2O, 6-11% CaO, 0.5-2% MgO and 0.5-2% Al2O3, based on a mass ratio of 100%.

3. The method according to claim 2, characterized in that In step (1), the amount of each raw material added to the liquid system is measured according to the component ratio of the hollow glass microspheres prepared in step (3).

4. The method according to any one of claims 1 to 3, characterized in that: In step (3), the silane coupling agent is selected from vinyl trimethoxy silane (A171), vinyl triethoxy silane (A172) or γ-methacryloxypropyl trimethoxy silane (KH570).

5. The method according to any one of claims 1 to 4, characterized in that: In step (3), the mass of the silane coupling agent is 1-3% of the precursor particles.

6. The method according to any one of claims 1 to 5, characterized in that: Step (3) is carried out in a vitrification gasification furnace.

7. The method according to claim 6, characterized in that Step (3) is specifically as follows: spraying the silane coupling agent into a vitrification gasification furnace in a convection manner, mixing it with the precursor particles for in-situ modification, and vitrification sintering to obtain surface-modified hollow glass microspheres.

8. The method according to any one of claims 1 to 7, characterized in that: In step (3), the sintering temperature is 700-900°C.

9. The method according to any one of claims 6 to 8, characterized in that: In step (3), the flight time of the precursor particles in the vitrification gasification furnace is about several seconds, for example, about 1-2 seconds.

10. The method according to any one of claims 1 to 9, characterized in that: In step (4), the mass percentage of the hollow glass microspheres in the polyphenylene ether resin is 5-60%.

Citation Information

Patent Citations

  • Hydrophobic hollow glass microsphere preparation method and prepared hydrophobic hollow glass microsphere thereof

    CN101781083A

  • Method for producing hollow glass microspheres on large scale through surface modification

    CN102321394A

  • Method for processing surface of hollow glass microsphere

    CN102504609A

  • Soft chemical preparation method for hollow glass micro-balloon, prepared hollow glass micro-balloon and application thereof

    CN102583973A

  • Polyphenyl ether resin-based composite material, and preparation method and application thereof

    CN110746763A